Gut Microbiota and its Metabolites in Pathogenesis of NAFLD - M. S. Reshetova; O. Yu. Zolnikova; V. T. Ivashkin; K. V. Ivashkin; S. A. Appolonova; T. L. Lapina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to provide information on the results of recent scientific research in the field of non-alcoholic fatty liver disease (NAFLD) metabolomic profiling.Key points. Metabolites of microbial origin are important biological molecules involved in many specific reactions of the human body. This literature review presents the results of recent studies in the field of metabolomics in patients with NAFLD. A more detailed understanding of the role of individual metabolites or their combinations in the NAFLD pathogenesis will allow us to determine the vector of further diagnostic and therapeutic approaches for this nosology. The research results of the probiotics effect on the levels of certain metabolites are currently being discussed.Conclusion. New research data in the field of studying the human metabolomic profile are presented. The results allow us to summarize the effects of microbial agents and their metabolites in the formation of changes in the liver parenchyma in the context of NAFLD. Changes in the level of endogenous ethanol, secondary bile acids, aromatic amino acids, branched chain amino acids, etc. have been described. Correlation between metabolites and certain bacterial strains has been established. A correlation between the ratio of bacteria types and clinical/laboratory parameters was noted in patients taking prebiotics.